Recognition and enforcement of declaratory awards under English Law as an effective method to protect the arbitration agreement - Pérez Font, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Where a party to an English arbitration clause commences proceedings before the courts of a state member of the EU other than the United Kingdom, the counterparty can: either claim for the stay of the proceedings before that Court, or start arbitral proceedings in England in order to obtain a declaratory ruling on the validity of the agreement which could subsequently be converted into a judgment under section 66 of the Arbitration Act 1996. In accordance with Article 45(1)(c) of Brussels I Bis Regulation, this judgment entered in the terms of the award would entitle the complying party to resist within the United Kingdom the enforcement of a later inconsistent Regulation judgment rendered in another state member.
Keywords: declaratory awards; oorpedo actions; s.66 Arbitration Act 1996; Article 45(1)(c) Brussels I Bis Regulation; enforcement of arbitral awards